2022
DOI: 10.1002/phar.2687
|View full text |Cite
|
Sign up to set email alerts
|

The safety of rapid infusion levetiracetam: A systematic review

Abstract: Epilepsy is a common diagnosis in the United States and a seizure can quickly progress to status epilepticus. In 2015, the number of adults with active epilepsy was estimated at 3 million, and the number of children with active epilepsy was estimated at 470,000.Active epilepsy includes the diagnosis of epilepsy and taking medication to control it, one or more seizures in the past year, or both. This amounts to 1.2% of the United States population with active epilepsy. 1 Seizures in an acute care setting need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Another retrospective review of 33 adult patients in the ICU showed that there was no difference in side effects in the 16 patients who received an undiluted bolus over 3–5 min and the 17 patients who received an infusion at a rate of 200–400 mg/hr (Burakgazi, Bashir, Doss, & Pellock, 2014). A recent systematic review of nine articles investigated rapid levetiracetam administration over 5 min, with doses ranging from 280 to 4,500 mg (Jense, Douville, & Weiss, 2022). The authors concluded that the administration of intravenous levetiracetam at a fast rate appears to be safe and tolerable via a peripheral line with few adverse effects, suggesting that SE treatment may be safely expedited by administering it more rapidly than other agents.…”
Section: Antiepilpetic Drugsmentioning
confidence: 99%
“…Another retrospective review of 33 adult patients in the ICU showed that there was no difference in side effects in the 16 patients who received an undiluted bolus over 3–5 min and the 17 patients who received an infusion at a rate of 200–400 mg/hr (Burakgazi, Bashir, Doss, & Pellock, 2014). A recent systematic review of nine articles investigated rapid levetiracetam administration over 5 min, with doses ranging from 280 to 4,500 mg (Jense, Douville, & Weiss, 2022). The authors concluded that the administration of intravenous levetiracetam at a fast rate appears to be safe and tolerable via a peripheral line with few adverse effects, suggesting that SE treatment may be safely expedited by administering it more rapidly than other agents.…”
Section: Antiepilpetic Drugsmentioning
confidence: 99%
“…4 Although there is limited evidence supporting faster infusion times in pediatric patients, many institutions report infusing the drug at a faster rate than the recommended 15-min infusion, based on use in several prospective randomized trials. 3,5,[6][7][8] Literature evaluating undiluted levetiracetam administration is limited to date, especially in the pediatric population. Three retrospective studies published over the last 2 years in adults have evaluated the use of rapid undiluted levetiracetam in doses ranging from 500 to 4500 mg.…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturer package labeling, levetiracetam vials for intravenous preparation must be diluted prior to use and infused over 15 min 4 . Although there is limited evidence supporting faster infusion times in pediatric patients, many institutions report infusing the drug at a faster rate than the recommended 15‐min infusion, based on use in several prospective randomized trials 3,5,6–8 . Literature evaluating undiluted levetiracetam administration is limited to date, especially in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Levetiracetam is safe with the most common adverse effects being mild. 11-15 In a recent study of 199 adult patients who received 1626 total doses of undiluted IV LEV (maximum 1000 mg), only 1.5% experienced agitation, delirium, confusion, and/or lethargy. 10 This study called for further assessment of safety for undiluted administration with regard to higher doses of LEV.…”
Section: Introductionmentioning
confidence: 99%